Measuring cross-sector collaboration an effective solution for solving unlicensed mining problems in Kuantan Singingi, Indonesia. Issue 1 (1st June 2022) - Tiyas Tinov, MY; Mulyadi, Aras; Sujianto; Zulkarnain; Putra, Ardi; Mutia, Tika; Handoko, Tito
Abstract: The research question of this paper is to explore success in eradicating unlicensed mining activities with a cross-sector collaboration approach. Mining workers without permits are of concern in many sectors because they refer to state assets. The mining sector requires an effective policy governance approach, through well-integrated planning actions between government, security or police agencies, NGOs, local communities and the role of the private sector. To explore possible implementation problems by following factors that influence government policy in dealing with unlicensed mining. The method used in this paper is a qualitative descriptive approach. Data sources are secondary and premier data. Premiere data were obtained from the results of in-depth interviews with relevant informants during the research conducted. The paper locus of this research is Kuantan Singingi Regency, Riau Province, Indonesia. The analysis used refers to the systematic literature review approach to the concept of cross-sector collaboration. The paper concludes with a discussion of the important factors underlying the emergence of unlicensed mining, the fundamental obstacles in eradicating them, how the government's plan of action to create a cross-sector collaboration as an effective solution to resolve the unlicensed mining problems.